PENGARUH PEMAHAMAN AKUNTANSI, SISTEM PENGENDALIAN INTERNAL, DAN TEKNOLOGI INFORMASI PADA KUALITAS LAPORAN KEUANGAN LPD SE-KOTA DENPASAR - Ni Komang Yuliana Letisya; I Putu Nuratama (UNHI Press, 2022)
The quality of financial statements is the result or achievement that has been achieved in managing company assets. This study aims to determine the effect of understanding accounting, internal control system, and information technology on the quality of financial statements of LPDs throughout Denpasar City. The population and sample in this study were the chief of the LPD and the Internal Auditor of the LPD at 35 LPDs throughout Denpasar City. The sampling technique used is a non-probability sampling technique which includes saturated sampling. The data were tested using validity test, reliability test, multicollinearity test, heteroscedasticity test, multiple regression analysis, hypothesis testing and coefficient of determination. The results showed that the variables of accounting understanding, internal control system, and information technology both had a positive and significant effect on the quality of financial statement at LPDs throughout Denpasar City.